Stochastic Dynamic Response of Dam-Reservoir Systems to Spatially Varying Earthquake Ground Motions - Bilici, Y.; Bayraktar, A.; Soyluk, K.; Hacıefendioğlu, K.; Ateş, S.; Adanur, S. (Elsevier Sci Ltd, 2009)
In this paper, stochastic dynamic responses of dam-reservoir-foundation systems subjected to spatially varying earthquake ground motions are investigated using the displacement-based fluid finite elements. For this purpose, variable-number-node two-dimensional (2D) fluid finite elements based on the Lagrangian approach is programmed in FORTRAN language and incorporated into a computer program SVEM, which is used for stochastic dynamic analysis of solid systems subjected to spatially varying earthquake ground motion. The spatially varying earthquake ground motion model includes incoherence, wave-passage and site-response effects. The incoherence effect is examined by considering the Harichandran and Vanmarcke coherency model. The effect of the wave passage is investigated by using various wave velocities. Homogeneous medium and firm soil types are selected for considering the site-response effect where the foundation supports are constructed. The Sari{dotless}yar concrete gravity dam, constructed in Turkey is selected for numerical example. The ground motion is described by filtered white noise and applied to each support point of the 2D finite element model of the dam-reservoir-foundation system. The record of Kocaeli earthquake in 1999 is used in the analyses. Displacements, stresses and hydrodynamic pressures occurring on the upstream face of the dam are calculated for four cases. It is concluded that spatially varying earthquake ground motions have important effects on the stochastic dynamic response of dam-reservoir-foundation systems. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Dam-Reservoir-Foundation Interaction; Fluid Finite Element; Lagrangian Approach; Spatially Varying Earthquake Ground Motion; Stochastic Analysis